Long term digestive outcome of œsophageal atresia. (February 2022) - Aumar, Madeleine; Nicolas, Audrey; Sfeir, Rony; Seguy, David; Gottrand, Frédéric
Abstract: Œsophageal atresia is a rare neonatal malformation consisting in an interruption of the continuity of the œsophagus, with or without a tracheo-œsophageal fistula. Although mortality rate is now low and most cases can benefit from successful surgical repair soon after birth, morbidity –specially digestive and nutritional-remains high. Many of the adults born with œsophageal atresia will suffer from dysphagia, gastro-œsophageal reflux and/or œsophageal dysmotility, leading to nutritional consequences and quality of life impairment. Barrett's œsophagus, potential risk of œsophageal cancer as well as risk of anastomotic stenosis and eosinophilic œsophagitis justify transition to adulthood and a lifelong prolonged follow-up.